Clinical efficacy and safety of secukinumab in the treatment of generalized pustular psoriasis in the pediatric population: a systematic review of the literature - Wei, Kebo; Li, Ping; He, Xin; Yang, Dongyue; Lang, Jing; Lai, Lingyao; Xiao, Min (Frontiers in Medicine, 2024)
Background Generalized pustular psoriasis (GPP) is a severe type of psoriasis. The current treatment primarily relies on corticosteroids and immunosuppressants. In recent years, biologics have been increasingly utilized in the treatment of this disease, and have demonstrated good clinical efficacy. However, children and adolescents are primarily treated with immunosuppressants, which have limited clinical application due to the serious side effects they may cause. At the same time, the effectiveness of current treatments is unsatisfactory. Secukinumab has been widely reported to be effective and safe in treating this disease. However, there are still insufficient data on its use in treating GPP in children. Objective To conduct a systematic review of the existing literature on the use of secukinumab for treating generalized pustular psoriasis in children and adolescents, and to evaluate its clinical effectiveness and safety. Methods We conducted a systematic review of all the literature reporting on the treatment of GPP in children and adolescents with secukinumab. Results A total of 7 papers (46 patients) were included in this study. After 12 weeks of treatment, all 46 participants were able to achieve a GPPASI score of 90 or higher, with approximately 96% of patients achieving complete clearing of the lesions (GPPASI 100 or JDA0). Adverse events were reported in 8 patients, the rate of adverse reactions was approximately 17%. Conclusion The treatment of GPP in children and adolescents with secukinumab has a rapid onset of action and a high safety profile. However, the results of the literature may be influenced by publication bias.